Growth and Development of Self-Confidence in Extracurricular Tapak Suci Activities of Elementary School Students - Nurvitasari, Roidah Aisyah; Sutama, S; Adnan, Mazlini (Universitas Muhammadiyah Surakarta, 2024)
Purpose: It is very important to develop individuals who are independent, able to adapt, and dare to make decisions, which support success in academic and social aspects. The importance of self-confidence developed at the Integrat-ed Islamic Primary School of the Gemolong Al-Quran Interpretation Assem-bly in extracurricular tapak suci can be used as an effort for students to channel their talent interests. The research objectives in this article are two-fold. 1) Describing activities without hesitation. 2) Describe the courage to appear in public places. Methodology: Extracurricular activities can be used as an effort for students to channel their talent interests through tapak suci. The type and design of research in this article is qualitative ethnography. The subjects in this study were the principal, extracurricular coordinator teacher, tapak suci extracurricular coach, and students who participated in extracurricular activities at the Inte-grated Islamic Elementary School of Majelis Tafsir Al-Quran Gemolong. The data collection methods used were participant observation, in-depth inter-views, and document analysis. Data validity in this study uses triangulation with inductive data analysis techniques. Results: The results of the research, 1) Doing activities without hesitation shows that strong self-confidence can increase one's effectiveness and success in mak-ing decisions and acting decisively and confidently. 2) Extracurricular activi-ties will encourage students to be more confident in performing in public and participating more actively in achieving their potential and abilities. Applications/Originality/Value: This research analyzes data inductively on the growth of self-confidence in tapak suci extracurricular activities in elementary schools through ethno-graphic qualitative methods.